Long-term safety of targeted agents used to treat metastatic renal cell carcinoma: the issue is not the rate of adverse events over time, but the expertise needed to manage them - Porta, Camillo; Chiellino, Silvia (Translational Cancer Research; Vol 5, Supplement 3 (September 29, 2016): Translational Cancer Research, 2016)
Targeted agents have revolutionized the treatment of advanced renal cell carcinoma (RCC), greatly improving the survival of patients affected with once orphan disease.